Involvement of JMJ15 in the dynamic change of genome-wide H3K4me3 in response to salt stress - Shen, Yuan; Chi, Yuhao; Lu, Shun; Lu, Huijuan; Shi, Lei (Frontiers in Plant Science, 2022)
Post-translational histone modifications play important roles in regulating chromatin structure and transcriptional regulation. Histone 3 lysine 4 trimethylation (H3K4me3) is a prominent histone modification mainly associated with gene activation. Here we showed that a histone demethylase, JMJ15, belonging to KDM5/JARID group, is involved in salt stress response in Arabidopsis thaliana. Jmj15 loss-of-function mutants displayed increased sensitivity to salt stress. Moreover, knockout of JMJ15 impaired the salt responsive gene expression program and affected H3K4me3 levels of many stress-related genes under salt-stressed condition. Importantly, we demonstrated that JMJ15 regulated the expression level of two WRKY transcription factors, WRKY46 and WRKY70, which were negatively involved in abiotic stress tolerance. Furthermore, JMJ15 directly bound to and demethylated H3K4me3 mark in the promoter and coding regions of WRKY46 and WRKY70, thereby repressing these two WRKY gene expression under salt stress. Overall, our study revealed a novel molecular function of the histone demethylase JMJ15 under salt stress in plants.